A Theoretical Model for Anchored Geosynthetics in Pull-Out Tests. Issue 3 (2000) - Gurung, N.
Abstract : A theoretical model is presented for the pull-out response of strip anchor reinforcement based on a nonlinear elastic (hyperbolic) shear stress-displacement relationship for the soil-reinforcement interface. The interface pull-out mechanism has been simplified by formulating the boundary conditions for the anchor section. Additional terms for the soil-reinforcement interaction, which incorporate the anchor section, are also introduced. A new concept of an anchorage factor (anchor-to-strip reinforcement capacities), the relative stiffness, and the displacement parameters are defined to explain the pull-out behaviour. A parametric study is carried out for a range of relative stiffness values, interface shear stresses, and anchorage factors. The normalised load-displacement relationship and the variations of pull-out force and displacements with distance along the reinforcement, at different anchorage factors, are presented. Experimental pull-out test results for planar reinforcements are also examined/compared with the model using a zero anchorage factor. The model helps to evaluate the pull-out displacements, stresses, and strains along the length of the strip anchor reinforcement.